Collaborative design of IoT systems for smart cities with and for citizen participation - Alencar, Tatiana Silva de; Zaina, Luciana (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais Estendidos do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Urban populations have grown and consequently cities have turned increasingly to IoT. IoT helps cities to address complex urban challenges and enhance quality of life. This doctoral project investigates how co-design methodologies can be properly applied to effectively implement IoT solutions in smart cities. The research aims to develop a comprehensive framework that provides guidelines, procedures, and artifacts for supporting co-design in the complex smart cities ecosystem. The expected outcomes include a deeper understanding of co-design in smart city contexts and practical insights into stakeholder engagement and technology integration.